Social Values in Family Welfare Empowerment Activities in Anjir Serapat Muara Village - Ainun Cahya; Ersis Warmansyah Abbas; Rusmaniah Rusmaniah; Jumriani Jumriani; M. Ridha Ilhami (The Innovation of Social Studies Journal, 2024)
Lack of public awareness of the importance of health by starting from a healthy way of life. In addition, the lack of education and knowledge about healthy living is the main factor for people not wanting to do posyandu. Therefore, the existence of Family Welfare Empowerment (PKK) is very helpful in meeting basic needs so that families can be empowered and cared for. This study aims to describe the social values in PKK activities in Anjir Serapat Muara village. The method used in this study is a qualitative method, data collection techniques by way of observation, interviews and documentation. Data analysis includes data reduction, data presentation and verification/conclusion. The results of the research describe that the Family Welfare Empowerment work program in Anjir Serapat Muara Village has social values in the activities carried out, namely social values of responsibility, social values of cooperation, social values of caring, social values of empathy and social values of helping each other. The social value obtained is found in the Family Welfare Empowerment activity work program which is routinely carried out every month, namely the Posyandu work program.